Organosilica nanoparticles containing sodium borocaptate (BSH) provide new prospects for boron neutron capture therapy (BNCT): efficient cellular uptake and enhanced BNCT efficacy. Issue 9 (17th April 2023) - Laird, Mathilde; Matsumoto, Kotaro; Higashi, Yuya; Komatsu, Aoi; Raitano, Art; Morrison, Kendall; Suzuki, Minoru; Tamanoi, Fuyuhiko
Abstract : BSH-containing mesoporous organosilica nanoparticles improve the boron uptake into cells and enhance BNCT efficacy. Abstract : Boron neutron capture therapy (BNCT), a method based on the fission of boron-10 upon neutron irradiation, has emerged as an attractive option for radiation therapy. To date, the main drugs used in BNCT are 4-boronophenylalanine (BPA) and sodium borocaptate (BSH). While BPA has been extensively tested in clinical trials, the use of BSH has been limited, mainly due to its poor cellular uptake. Here, we describe a novel type of mesoporous silica-based nanoparticle containing BSH covalently attached to a nanocarrier. Synthesis and characterization of these nanoparticles (BSH-BPMO) are presented. The synthetic strategy involves a click thiol–ene reaction with the boron cluster, providing hydrolytically stable linkage with the BSH in four steps. The BSH-BPMO nanoparticles were efficiently taken up into cancer cells and accumulated in the perinuclear region. Inductively coupled plasma (ICP) measurements of boron uptake in cells highlight the important role of the nanocarrier in the enhancement of boron internalization. BSH-BPMO nanoparticles were also taken up and distributed throughout tumour spheroids. BNCT efficacy was examined by the neutron exposure of the tumour spheroids. BSH-BPMO loaded spheroids were completely destroyed upon neutron irradiation. In contrast, neutron irradiation of tumour spheroids loaded with BSH or BPA resulted in significantly less spheroid shrinkage. The significant difference in BNCT efficacy of the BSH-BPMO was correlated with the improved boron uptake via the nanocarrier. Overall, these results demonstrate the critical role of the nanocarrier in BSH internalization and the enhanced BNCT efficacy of the BSH-BPMO compared with BSH and BPA, two drugs used in BNCT clinical trials.